The effect of bisphenol on blood parameters and reproductive physiology status in male local breed rabbits - Al-Nuaimi, A. J.; Mahdi, Z. S.; Rahi, T. S.; Imams, N. A. A.; Jawad, M. N. (Scientific Progress & Innovations, 2025)
One of the most widely produced chemicals worldwide, bisphenol A is used in food and beverage packaging, water bottles, and dental sealants. Bisphenol A has become a possible hazard to many organisms, including public health, as a result of its widespread use. This research is aimed at showing the effect of bisphenol A on some hematological and reproductive parameters in male rabbits. The experiment was conducted from March 1, 2024, to May 2, 2025 at the University of Kerbala, the Faculty of Veterinary Medicine. The rabbits used in the experiment were housed in special cages. Twenty local breed rabbits were used, split into two groups. Every animal had been examined to ensure there were no injuries or anomalies before the experiment started. Ten rabbits in the control group (G1), were given tap water and pellets only, while group 2 (G2) was treated with bisphenol A (1 ml/kg) and additionally administered orally with water and pellets. The data from the experiment was analyzed using the SAS. In the second experiment, a one-way ANOVA was used, and the least significant differences (LSD) were utilized to ascertain whether the group indicators differed significantly. The results have shown that there are no significant differences in erythrocyte count between group 1 (C) and group 2 (T) after being treated with bisphenol A, while a significant decrease in hematological parameters such as leukocytes to 3.92 in the group treated with bisphenol suggested that bisphenol A has immunosuppressant action, also significant decrease in packed cell volume to 39.9 and hemoglobin concentration to 11.84 indicate that bisphenol A causes anemia. On the other hand, the reproductive hormones concentration shows that there is significant decrease in testosterone to 0.45 and estradiol 21.5 and indicate that bisphenol A cause hypogonadism in male rabbits. Thus, we see that bisphenol A has a negative effect on blood formation by significantly decreasing the packed cell volume ratio, hemoglobin concentration, white blood cells count and reproductive hormones (estrogen and testosterone concentrations) so it has a negative effect on rabbits’ health.